Ground surface temperature reconstruction for the Jinggangshan Mountains: Interpreting the hydro-thermal coupling pattern in southeastern China. (1st December 2020) - Cai, Qiufang; Liu, Yu; Fang, Congxi; Zhang, Hanyu; Song, Huiming; Li, Qiang; Sun, Changfeng; Wan, Chun; Liu, Ruoshi
Abstract: Understanding the spatial-temporal variations of climatic factors and hydro-thermal coupling patterns (HTCP) is crucial to forecasting and preparing for future climate change. Based on accurately dated tree rings, we developed the first dekad (10 days)-6 to dekad-27 minimum ground surface temperature (GSTmin6–27) reconstruction for the Jinggangshan Mountains (JGSM) in southeastern China (SC). Spanning the period 1791–2014 AD, this reconstruction explains 57.9% of observed temperature during the instrumental period (1960–2014 AD). Our record exhibits a slow cooling trend before 1834 AD, followed by drastic fluctuations between 1835 and 1850 AD, and progressive warming ( R 2  = 0.31) thereafter. The highest GSTmin6–27 variance occurs during the 1820s–1840s and from the 1900s to the early 1930s. Our reconstruction not only captures the characteristics of temperature variability over a large portion of SC, but also reveals decadal-scale temperature fluctuations that are approximately synchronous with conditions across North China and the Northern Hemisphere. This research suggests that the Western Pacific Subtropical High (WPSH) was likely the primary control of GSTmin6–27 variability in the JGSM, while the Pacific Decadal Oscillation (PDO), tropical Indian and western Pacific Ocean sea surface temperatures, along with the North Atlantic Oscillation (NAO), indirectly influenced decadal-scale temperature variations. Based on our new reconstruction, we identified regional, decadal-scale differences in the HTCP over SC, with an insignificant warm-dry (cold-wet) coupling pattern dominating the JGSM, and a significant warm-wet (cold-dry) pattern in coastal areas. Highlights: Ground surface temperature (GST) in southeastern China (SC) is less studied. The hydro-thermal coupling pattern (HTCP) of SC in the past is not clear. We developed a tree-ring-based GST record in SC since 1791 AD. GST variability was driven by large-scale air-sea interactions (WPSH, PDO, NAO). We identified regional, decadal-scale differences in the HTCP over SC.